Positivity and stability of fractional descriptor time-varying discrete-time linear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The Weierstrass-Kronecker theorem on the decomposition of the regular pencil is extended to fractional descriptor time-varying discrete-time linear systems. A method for computing solutions of fractional systems is proposed. Necessary and sufficient conditions for the positivity of these systems are established.
Keywords: fractional systems; descriptor systems; time-varying systems; positive systems; discrete-time systems